PENGARUH EKSPOR, IMPOR, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Dhea, Fita Faelasufa Kusuma (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2022)
The study's goal is to examine how long- and short-term changes in exports, imports, and inflation affect Indonesia's economic growth. Data was compiled from secondary sources including Central Statistics Agency and the World Bank's records from 1995-2020. EViews 10 was used to conduct a regression analysis utilizing an ARDL (Autoregressive Distributed Lag) model. According to the findings of the test of the analysis's short-term relevance, exports have a negative and insignificant influence, but imports and inflation have a positive and insignificant effect. Exports have a positive and major influence in the long run, whereas imports and inflation have a negative and major influence.